Pengaruh Modal Sendiri dan Total Aset Terhadap Perolehan Sisa Hasil Usaha Koperasi Pegawai Negeri Sekecamatan Buleleng - Putri, Kadek Rina Praba Wati; Suwendra, I Wayan (Universitas Pendidikan Ganesha, 2023)
Cooperatives are a form of business that contributes positively to Indonesian economic development and welfare by increasing the remaining results of cooperative operations. This study aims to examine the effect of own capital and total assets on the acquisition of the remaining business results of the Civil Servants Cooperative in Buleleng District. The data analysis method used in this study was the classical assumption test, multiple linear regression analysis, F test, t-test, and test the coefficient of determination (R2). The results of the research based on multiple linear regression analysis show that (1) there is an effect of own capital and total assets on the acquisition of the remaining business results of the Buleleng Sub-district Civil Servant Cooperative of 0.938, (2) there is an effect of own capital on the acquisition of the remaining business results of the Buleleng Sub-District Civil Servant Cooperative of 0.735, (3) there is an effect of total assets on the acquisition of the remaining results of the operations of the Buleleng Civil Servant Cooperative of 0.928. The test results for the coefficient of determination (R2) were 0.874 (87.4%), while the rest were influenced by other variables by 0.126 (12.6%).